Research on program load spectrum for key components of a metro vehicle body - Yongzhang, Su; Wenjia, He; Honglin, Duan; Xiao, Wu (Frontiers in Applied Mathematics and Statistics, 2025)
This study aims to construct a load spectrum that conforms to the actual working conditions, enabling an accurate fatigue life assessment of key components and enhancing the overall safety and reliability of the metro vehicle. A field test is first conducted on the mainline of a metro to collect the distribution of the random load data. Based on the load test data from the online operation of the test vehicle, the method of compiling the program load spectrum of the key components of the metro vehicle body is studied. The load data of the key components of the vehicle body are screened and interpreted to eliminate errors and peak disturbances in the signal. Using the rainflow counting method to analyze the time load series, the load data under actual road conditions are simplified and recorded. The probability distribution function of the load amplitude and load mean of the key components of the vehicle body is established using statistical methods. Based on its distribution characteristics, the frequency of rainflow counting is extrapolated. Combined with its joint probability distribution function, the load extreme value is obtained, and the 8-level two-dimensional load spectrum of the key components of the vehicle body is constructed. Furthermore, the variable mean method is used to simplify the two-dimensional load spectrum to obtain the one-dimensional load spectrum, and the HBM Ncode program is used to prepare the program load spectrum. The results show that the mean value of the load conforms to a Gaussian distribution with a mean value of 3.150 MPa and a standard deviation of 1.591 MPa. The load amplitude follows a two-parameter Weibull distribution, with a shape parameter of 1.882 and a scale parameter of 1.949. This provides a theoretical basis for the fatigue life assessment of the key components of the metro vehicle body.